Aliphatic polyesters, polyester compositions containing the same, and their use

JP2026149516A5Pending Publication Date: 2026-10-30KINGFA SCI & TECH CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026037603
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-10
Filing Date
2026-03-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

Existing starch-based biodegradable materials suffer from anisotropy and poor uniformity in tear properties, particularly in the longitudinal and transverse directions, and do not meet the requirements for home composting due to the use of aliphatic-aromatic polyesters like PBAT as the base resin.

Method used

The development of aliphatic polyesters comprising specific ratios of succinic acid and sebacic acid residues, controlled through polymerization, to produce polybutylene succinate sebacate with uniform tear properties, which are then used as a base resin for starch-based biodegradable materials.

Benefits of technology

The solution provides biodegradable materials with uniform longitudinal and transverse tear properties, ensuring good tensile properties and biodegradability, meeting the requirements for home composting.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention aims to provide aliphatic polyesters, polyester compositions containing the same, and their uses. [Solution] The present invention provides an aliphatic polyester, a polyester composition containing the same, and the use thereof. The aliphatic polyester comprises a dibasic acid residue and a diol residue. The dibasic acid residue comprises, as residues, a1): 61.2 to 69 mol% succinic acid residues based on a total mole fraction of a1) and a2) of 100 mol%, and a2): 31 to 38.8 mol% sebacic acid residues based on a total mole fraction of a1) and a2) of 100 mol%, and the diol residue is selected from at least an equimolar amount of 1,4-butanediol residues with respect to the dibasic acid residue. In the present invention, the aliphatic polyester has good uniformity in both longitudinal and transverse tear properties, and furthermore, has high tensile strength and a relatively short biodegradation cycle under home composting conditions, thus meeting the requirements for home composting.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention belongs to the technical field of biodegradable polyester materials, and more specifically, to aliphatic polyesters, polyester compositions containing the same, and the use thereof. [Background technology]

[0002] Resource and environmental issues are major challenges that humanity faces in achieving sustainable development. Among these, environmental pollution is one manifestation of resource and environmental problems. For example, white pollution caused by general-purpose plastics, especially packaging films such as shopping bags, garbage bags, and agricultural mulch films, has a serious impact on land use efficiency, causes air and water pollution, is prone to fire, and also affects people's health. White pollution is a phenomenon in which used plastics are carelessly discarded and pollute the environment because they are difficult to decompose. Therefore, the development of high-performance biodegradable materials is one of the important and indispensable means to solve white pollution.

[0003] Biodegradable materials are typically filled with polymers derived from natural resources such as starch to reduce costs and improve film flexibility. However, commercially available starch-based biodegradable materials have problems with poor uniformity of mechanical properties, particularly in terms of tear strength in the transverse and longitudinal directions. Such biodegradable materials are prone to tearing transversely and therefore cannot withstand certain weight limits. Furthermore, many commercially available starch-based biodegradable materials use aliphatic-aromatic polyesters such as polybutylene adipate terephthalate (PBAT) or polybutylene sebacate terephthalate (PBSeT) as the base resin. Because aliphatic-aromatic polyesters contain relatively high amounts of terephthalate segments in their molecular structure, they often do not meet the requirements for home composting when the product thickness is relatively large (>50 μm).

[0004] To address the challenges of uniformity in mechanical properties in starch-based biodegradable materials, particularly the anisotropy of tear properties in the longitudinal and transverse directions, CN101522797A discloses a biodegradable composition that effectively improves material anisotropy by using starch with an average particle size of less than 0.25 μm as the dispersed phase. However, the finer the starch particles, the higher the cost, and dispersion becomes difficult in highly packed systems. Furthermore, because the composition uses PBAT as the base resin, it cannot effectively solve the material challenges in home composting.

[0005] Based on this, the development of aliphatic polyesters suitable for the production of starch-based biodegradable materials that exhibit good uniformity in both longitudinal and transverse tearing properties, have a high decomposition rate, and meet the requirements for home composting is an urgent issue that needs to be addressed in this field. [Overview of the Initiative] [Problems that the invention aims to solve]

[0006] The present invention aims to provide aliphatic polyesters, polyester compositions containing them, and their use, in order to overcome the shortcomings of the prior art. The aliphatic polyesters can be used in the production of starch-based biodegradable materials, solving problems such as the anisotropy and poor uniformity of the longitudinal and transverse tear properties of starch-based biodegradable materials, and meeting the requirements for composting at home. [Means for solving the problem]

[0007] To achieve this objective, the present invention employs the following technical solutions.

[0008] In a first aspect, the present invention provides an aliphatic polyester comprising a dibasic acid residue and a diol residue, wherein the dibasic acid residue comprises, as residues, a1): 61.2 to 69 mol% succinic acid residues based on a total mole fraction of a1) and a2) of 100 mol%, and a2): 31 to 38.8 mol% sebacic acid residues based on a total mole fraction of a1) and a2) of 100 mol%, and the diol residue is selected from at least an equimolar amount of 1,4-butanediol residues with respect to the dibasic acid residue. In the present invention, by controlling the content of succinic acid residues and sebacic acid residues within the above ranges, a polybutylene succinate sebacate with uniform lateral and longitudinal tear properties can be obtained. By preparing a starch-based biodegradable material using the aforementioned polybutylene succinate sebacate as a base resin, it is possible to solve problems such as poor anisotropy and uniformity of the lateral and longitudinal tear properties of starch-based biodegradable materials, and to ensure that the material has good tensile properties and decomposability, thereby meeting the requirements for composting at home.

[0009] The term "residue" refers to any organic structure introduced into the polymer molecular chain by related monomers through polycondensation reactions, i.e., an organic structure derived from related monomers. For example, a dibasic acid residue refers to a structure derived from a dibasic acid monomer in an aliphatic polyester.

[0010] In this invention, succinic acid and / or succinic acid derivatives are introduced into the molecular chain of polyester through a polymerization reaction to form succinic acid residues. Sebacic acid and / or sebacic acid derivatives are introduced into the molecular chain of polyester through a polymerization reaction to form sebacic acid residues. In the segment structure of the aliphatic polyester, a high content of succinic acid residues results in a fast crystallization rate, high degree of crystallinity, and poor uniformity of tear properties in the longitudinal and transverse directions. A high content of sebacic acid residues makes the aliphatic polyester segment flexible and similarly worsens the uniformity of tear properties in the longitudinal and transverse directions. By controlling the molar ratio of succinic acid residues to sebacic acid residues within a specific range, the aliphatic polyester can have excellent uniformity of tear properties in the longitudinal and transverse directions without affecting the processing performance of the material, while ensuring good tensile properties and degradability.

[0011] In the present invention, the succinic acid derivative includes an alkyl succinate, and exemplary the alkyl succinate may be at least one of dimethyl succinate, diethyl succinate, di-n-propyl succinate, diisopropyl succinate, di-n-butyl succinate, diisobutyl succinate, di-tert-butyl succinate, di-n-pentyl succinate, diisopentyl succinate, and di-n-hexyl succinate. The alkyl succinate may be an alkyl ester formed from succinic acid, or an alkyl ester formed from succinic anhydride, and preferably dimethyl succinate formed from succinic anhydride.

[0012] In the present invention, the sebacate derivative comprises an alkyl sebacate, and exemplary the alkyl sebacate may be at least one of dimethyl sebacate, diethyl sebacate, di-n-propyl sebacate, diisopropyl sebacate, di-n-butyl sebacate, diisobutyl sebacate, di-tert-butyl sebacate, di-n-pentyl sebacate, diisopentyl sebacate, or di-n-hexyl sebacate. The alkyl sebacate may be an alkyl ester formed from sebacate or an alkyl ester formed from sebacate anhydride.

[0013] Preferably, the dibasic acid residue comprises, as a1): 63.5 to 67.5 mol% succinic acid residues based on a total mole fraction of 100 mol% of a1) and a2), and, as a2): 32.5 to 36.5 mol% sebacic acid residues based on a total mole fraction of 100 mol% of a1) and a2).

[0014] Preferably, the number-average molecular weight (Mn) of the aliphatic polyester is 30,000 to 150,000, preferably 45,000 to 120,000, and more preferably 58,000 to 79,000.

[0015] In this invention, the number-average molecular weight can be measured by gel permeation chromatography (GPC) using monodisperse polystyrene as a standard substance. Both excessively high and low number-average molecular weights cause a decrease in the uniformity of the longitudinal and transverse tear properties of aliphatic polyesters.

[0016] In this invention, the number-average molecular weight can be controlled by adjusting the polymerization temperature and time, or by adding crosslinking agents, chain transfer agents, etc.

[0017] Preferably, in accordance with GB / T 32366-2015, the carboxyl content of the aliphatic polyester is <35 mol / t, preferably <28 mol / t, and more preferably 5 to 20 mol / t.

[0018] In this invention, the aliphatic polyester has poor hydrolysis resistance and aging resistance due to its high carboxyl content, while a low carboxyl content results in a low biodegradability and higher costs. The fewer unreacted carboxylic acid terminals derived from the dicarboxylic acid component, the lower the carboxyl content of the aliphatic polyester. Therefore, the carboxyl content can be controlled by adjusting the degree of reactivity or suppressing thermal decomposition by changing conditions such as the ratio of alcohol to acid, polymerization temperature, and polymerization time. Furthermore, the carboxyl content can also be controlled by suppressing the type and amount of impurities in the raw materials, such as nitrogen compounds and metal ions.

[0019] Preferably, in accordance with GB / T 17931-1999, the intrinsic viscosity of the aliphatic polyester is 1.38 to 2.32 dL / g, more preferably 1.5 to 2.2 dL / g, more preferably 1.58 to 2.11 dL / g, more preferably 1.67 to 2.02 dL / g, and most preferably 1.82 to 1.95 dL / g.

[0020] In this invention, because the intrinsic viscosity of the aliphatic polyester is within the above range, the aliphatic polyester has good uniformity in its tear properties in the longitudinal and transverse directions, and the mechanical properties of the molded article during molding are ensured. Furthermore, it is ensured that the melt viscosity of the polyester during molding does not place an excessive load on molding machines such as extruders and injection molding machines, thereby ensuring productivity.

[0021] In the present invention, the method for producing the aliphatic polyester is not particularly limited, and any method capable of producing an aliphatic polyester having the specific structure of the present invention is acceptable. Preferably, the method for producing the aliphatic polyester is: Step (1) of reacting a dibasic acid with a diol to obtain an esterification product, Step (2) of subjecting the esterification product obtained in Step (1) to a prepolymerization reaction to obtain a prepolymerization product, Step (3) of subjecting the prepolymerization product obtained in Step (2) to a polycondensation reaction to obtain a polycondensation product, that is, the aliphatic polyester of the present invention.

[0022] In the present invention, the dibasic acid in Step (1) is succinic acid and / or a succinic acid derivative, and sebacic acid and / or a sebacic acid derivative. The dibasic acid may be used alone or may be a mixture of at least two kinds thereof. The diol is 1,4-butanediol.

[0023] In the present invention, the molar ratio of the diol to the dibasic acid is (1.2 to 3):1, and may be, for example, 1.2:1, 1.5:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, or a range between any of the above numerical values, and more preferably (1.4 to 2):1.

[0024] In the present invention, the origin of the succinic acid and / or succinic acid derivative is not particularly limited, and may be bio-based succinic acid and / or succinic acid derivative (that is, the production raw material is biomass resource), or may be petroleum-based succinic acid and / or succinic acid derivative (that is, the production raw material is petroleum resource).

[0025] In the present invention, step (1) the raw materials for the reaction further comprises a crosslinking agent, wherein the total mass of the aliphatic polyester is 100 wt%, and the mass of the crosslinking agent is 0 to 3 wt%, and the crosslinking agent comprises at least one of polyols, polybasic acids, or polybasic acid anhydrides. Exemplary examples of the crosslinking agent include, but are not limited to, tartaric acid, citric acid, malic acid, trimethylolpropane, trimethylolethane, pentaerythritol, polyethertriol, glycerin, trimesic acid, trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromellitic dianhydride, etc.

[0026] In the present invention, the reaction in step (1) includes an esterification reaction and / or a transesterification reaction. The reaction is carried out at a temperature of 150 to 220°C, a pressure of 0.7 to 1.3 bar, and for a duration of 2 to 6 hours, and more preferably at a temperature of 165 to 210°C, a pressure of 0.8 to 1.2 bar, and for a duration of 3 to 5 hours.

[0027] In the present invention, step (1) may be carried out in a single mixing apparatus, in which a dibasic acid and a diol are mixed to obtain a slurry, and then the temperature is raised to allow the reaction to proceed.

[0028] In the present invention, step (1) the carboxyl content of the esterification product is 240 to 570 mol / t, more preferably 300 to 400 mol / t.

[0029] In this invention, after the reaction in step (1), the present invention further includes a step of removing excess diol by distillation, and the removed diol can be recycled as a raw material after purification by distillation. The purity of the purified diol is ≥95%.

[0030] In the present invention, the preliminary polymerization reaction in step (2) is carried out at a temperature of 230 to 260°C, a pressure of 0.3 to 0.8 bar, and for a duration of 70 to 200 min, and more preferably, the reaction is carried out at a temperature of 240 to 250°C, a pressure of 0.5 to 0.7 bar, and for a duration of 90 to 130 min.

[0031] In the present invention, step (2) may be carried out in a single prepolymerization reactor.

[0032] In the present invention, the carboxyl content of the prepolymerization product in step (2) is 40 to 90 mol / t, more preferably 55 to 75 mol / t.

[0033] In the present invention, step (3) the polycondensation reaction is carried out at a temperature of 235 to 260°C, a pressure of 0.2 to 5 mbar, and a time of 40 to 110 min, and more preferably, the reaction is carried out at a temperature of 240 to 250°C, a pressure of 0.5 to 2 mbar, and a time of 70 to 100 min.

[0034] In the present invention, step (3) can be carried out in a finishing apparatus suitable for polycondensation reactions, such as a rotary reactor, a cage reactor, or a horizontal reactor.

[0035] In the present invention, the reaction in step (2) is carried out in the presence of a catalyst. The catalyst may be a tin compound, an antimony compound, a cobalt compound, a lead compound, a zinc compound, an aluminum compound, or a titanium compound, more preferably a zinc compound, an aluminum compound, or a titanium compound, and most preferably a titanium compound. The titanium compound may be tetrabutyl titanate or tetraisopropyl titanate. Compared to other compounds, the titanium compound phase has lower residue levels in the product and downstream products, and is also less toxic. It is particularly suitable for the production of biodegradable polyesters and can be directly introduced into the environment in the form of compost bags or coating films.

[0036] In this invention, the total mass of the reaction raw materials (dibasic acid, diol, and optional crosslinking agent) is 100 wt%, and the total mass of the catalyst is 0.001 to 1 wt%.

[0037] In this invention, other auxiliary agents may be added during the reaction in step (3) depending on the actual needs. These other auxiliary agents include, but are not limited to, catalyst passivators, color stabilizers, and activators.

[0038] The catalyst passivator includes, but is not limited to, a phosphorus compound. The phosphorus compound includes, but is not limited to, one or more of phosphorous acid and phosphoric acid. With a prepolymerization product mass of 100 wt%, the mass of the catalyst passivator is 0.001 to 0.1 wt%, preferably 0.01 to 0.05 wt%. Exemplarily, when a highly active titanium compound is used as the catalyst, a catalyst passivator can be added. Here, the molar ratio of Ti to P is (1.1 to 1.5):1, and particularly preferably, the molar ratio of Ti to P is (1.1 to 1.3):1.

[0039] The color stabilizer includes, but is not limited to, a phosphorus compound. The phosphorus compound includes, but is not limited to, one or more of phosphoric acid, phosphorous acid, triphenyl phosphate, triphenyl phosphate, sodium hypophosphite, and sodium phosphate. The use of a color stabilizer usually reduces the condensation rate. Therefore, triphenyl phosphate is preferably used as a color stabilizer because it does not adversely affect the condensation rate. With a prepolymerization product mass of 100 wt%, the mass of the color stabilizer is 0.001 to 1.5 wt%, preferably 0.01 to 1.0 wt%. When the catalyst is selected from titanium compounds, the molar ratio of Ti to P is 1:(0.3 to 1.0), particularly preferably 1:(0.5 to 1.0).

[0040] The activator includes, but is not limited to, a phosphorus compound. The phosphorus compound includes, but is not limited to, one or more of the following: disodium hydrogen phosphate, calcium hypophosphite, calcium phosphite, calcium phosphate, sodium hypophosphite, sodium phosphite, triphenyl phosphite, triphenyl phosphate, trimethyl phosphate, triethyl phosphate, tripropyl phosphate, and tributyl phosphate. With the mass of the prepolymerization product being 100 wt%, the mass of the activator is 0.001 to 1.5 wt%, preferably 0.01 to 1.0 wt%. When the catalyst is selected from titanium compounds, the molar ratio of Ti to P is (1.0 to 1.5):1, particularly preferably (1.1 to 1.3):1.

[0041] More preferably, the color stabilizer and the activator are used in combination, for example, triphenyl phosphate and disodium hydrogen phosphate are used in combination.

[0042] The present invention further includes a chain extension reaction in which, after the polycondensation reaction, the product obtained by the polycondensation reaction (polycondensation product) is reacted with a chain extender to obtain the aliphatic polyester.

[0043] In the present invention, the chain extender comprises one or more of the following: isocyanate, peroxide, epoxide, oxazoline, oxazine, caprolactam, or carbodiimide.

[0044] In the present invention, the isocyanate may be an aromatic diisocyanate and / or an aliphatic diisocyanate, and the aromatic diisocyanate may be toluene 2,4-diisocyanate, toluene 2,6-diisocyanate, diphenylmethane 2,2'-diisocyanate, diphenylmethane 2,4'-diisocyanate, diphenylmethane 4,4'-diisocyanate, 1,5-naphthalene diisocyanate or xylene diisocyanate, but particularly preferably diphenylmethane 2,2'-diisocyanate, diphenylmethane 2,4'-diisocyanate or diphenylmethane 4,4'-diisocyanate is used. The aromatic diisocyanate may be a polynuclear aromatic diisocyanate, for example, tris(4-isocyanatophenyl)methane having three rings that can be formed when producing a diisocyanate having one or two rings. The aliphatic diisocyanate may be a linear or branched alkylene diisocyanate having 2 to 20 carbon atoms, or a cycloalkylene diisocyanate having 3 to 20 carbon atoms. Exemplarily, the aliphatic diisocyanate includes hexamethylene diisocyanate, pentamethylene diisocyanate, isophorone diisocyanate, or methylenebis(4-isocyanetocyclohexane) diisocyanate. Hexamethylene diisocyanate is particularly preferred.

[0045] In the present invention, based on the total mass of the polycondensation product, the mass of the isocyanate may be 0.05 to 2 wt%, but is particularly preferably 0.1 to 1.5 wt%.

[0046] In the present invention, the peroxide may be one or more of the following: benzoyl peroxide, 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(tert-butylperoxy)methylcyclododecane, n-butylbis(4,4-tert-butylperoxy)valerate, dicumyl peroxide, tert-butylperoxybenzoate, dibutyl peroxide, α,α-di(tert-butylperoxy)diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexa-3-yne, or tert-butylcumeneperoxide.

[0047] In the present invention, based on the total mass of the polycondensation product, the mass of the peroxide may be 0.1 to 2 wt%, but is particularly preferably 0.2 to 1 wt%.

[0048] In the present invention, the epoxide may be one or more copolymers containing epoxy groups based on diglycidyl ether, hexamethylene diglycidyl ether, sorbitol diglycidyl ether, polyglycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, diglycerol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, resorcinol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, dipropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, and polybutylene glycol diglycidyl ether, styrene, acrylate and / or methacrylate.

[0049] In this invention, based on the total mass of the polycondensation product, the mass of the epoxide may be 0.1 to 2 wt%, but is preferably 0.2 to 1 wt%.

[0050] In the present invention, the oxazoline may be one or more selected from 2,2'-bis(2-oxazoline), bis(2-oxazolinyl)methane, 1,2-bis(2-oxazolinyl)ethane, 1,3-bis(2-oxazolinyl)propane, 1,4-bis(2-oxazolinyl)butane, 1,4-bis(2-oxazolinyl)benzene, 1,2-bis(2-oxazolinyl)benzene, or 1,3-bis(2-oxazolinyl)benzene. The oxazine may be one or more selected from 2,2'-bis(2-dioxazine), bis(2-dioxazinyl)methane, 1,2-bis(2-dioxazinyl)ethane, 1,3-bis(2-dioxazinyl)propane, 1,4-bis(2-dioxazinyl)butane, 1,4-bis(2-dioxazinyl)benzene, 1,2-bis(2-dioxazinyl)benzene, or 1,3-bis(2-dioxazinyl)benzene. The carbodiimide may be one or more selected from N,N'-di-2,6-diisopropylphenylcarbodiimide, N,N'-di-o-tolylcarbodiimide, N,N'-diphenylcarbodiimide, N,N'-dioctyldecylcarbodiimide, N,N'-di-2,6-dimethylphenylcarbodiimide, N-tolyl-N'-cyclohexylcarbodiimide, N,N'-di-2,6-di-tert-butylphenylcarbodiimide, N,N'-di-2,4,6-triisobutylphenylcarbodiimide, diisopropylcarbodiimide, dimethylcarbodiimide, diisobutylcarbodiimide, dioctylcarbodiimide, tert-butylisopropylcarbodiimide, di-β-naphthylcarbodiimide, or di-tert-butylcarbodiimide.

[0051] In the present invention, based on the total mass of the polycondensation product, the masses of oxazoline, oxazine, caprolactam, and carbodiimide are each independently 0.1 to 2 wt%, preferably 0.2 to 1 wt%.

[0052] In this invention, the temperature of the chain extension reaction is 170 to 240°C, and more preferably, the reaction temperature is 180 to 220°C. Depending on the system used, the reaction is carried out under ultra-high pressure or atmospheric pressure.

[0053] In this invention, the chain extension reaction can be carried out in an extruder, a continuous kneader (List reactor), or a static mixer. The extruder may be a single-screw or twin-screw extruder. The static mixer can use SMR, SMX, or SMXL components, or a combination thereof. Examples of List reactors include single-screw DISCOTHERM B, twin-screw CRP, or ORP reactors. Preferably, the chain extension reaction is carried out in an extruder, with a residence time of 2 to 15 minutes, more preferably 4 to 10 minutes.

[0054] In the present invention, the aliphatic polyester can also be produced by reacting succinic acid and / or a succinic acid derivative with 1,4-butanediol in step (1) to obtain two types of esterified products, and then subjecting the two types of esterified products to subsequent prepolymerization reactions, polycondensation reactions, and optional chain extension reactions.

[0055] For example, the manufacturing method specifically includes the following steps:

[0056] Step (1-1): Succinic acid and / or succinic acid derivatives, 1,4-butanediol, and an optional crosslinking agent are reacted for 2-5 hours under conditions of a temperature of 150-180°C and a pressure of 0.7-1.1 bar to obtain esterification product A having a carboxyl content of 450-750 mol / t.

[0057] Step (1-2): Sebacic acid and / or a sebacic acid derivative is reacted with 1,4-butanediol at a temperature of 180-210°C and a pressure of 0.6-1.1 bar for 3-6 hours to obtain esterification product B with a carboxyl content of 300-620 mol / t. Then, esterification product A and esterification product B are mixed and subjected to prepolymerization, polycondensation, and optional chain extension reactions. Here, the conditions for the prepolymerization, polycondensation, and optional chain extension reactions are selected from the same range as in Step (2), Step (3), and the chain extension reaction described above.

[0058] In a second aspect, the present invention provides a polyester composition comprising polymer A and polymer B, wherein polymer A comprises the aliphatic polyester described in the first aspect.

[0059] Preferably, the polymer A further comprises a second polyester.

[0060] Preferably, the second polyester comprises at least one of polylactic acid (PLA), aliphatic-aromatic polyester, or other aliphatic polyester.

[0061] Preferably, the aliphatic-aromatic polyester comprises at least one of polybutylene succinate terephthalate (PBST), polybutylene adipate terephthalate (PBAT), polybutylene sebacate terephthalate (PBSeT), or polybutylene adipate diflangecarboxylate (PBAF).

[0062] Preferably, the other aliphatic polyester comprises at least one of polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), or polybutylene sebacate (PBSe).

[0063] In the present invention, the second polyester can be selected according to the actual needs and is not limited to the polyester described above.

[0064] Preferably, the polymer B comprises at least one of the following: starch, cellulose, chitin, chitosan, alginate ester, protein, gelatin, natural rubber, lignin, or a derivative of the aforementioned substances.

[0065] In this invention, the protein includes, but is not limited to, gluten, zein, casein, and collagen. The lignin includes unrefined lignin, purified hydrolyzed lignin, alkalized lignin, and the like. Starch can be used in allosteric form, gelled form, or filler form. The starch may represent a continuous phase or a dispersed phase, or it may be in a cocontinuous form.

[0066] Preferably, the polyester composition further comprises an auxiliary agent.

[0067] In the present invention, the auxiliary agent may be added according to the actual needs and may include, but is not limited to, at least one of the following: an antioxidant, a lubricant, a light stabilizer, a mold release agent, or an antistatic agent.

[0068] In the present invention, the type of auxiliary agent is not particularly limited, and any ordinary auxiliary agent may be used. For example, the antioxidant includes, but is not limited to, any one of antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 164, antioxidant DLTP, or antioxidant TPP.

[0069] The aforementioned light stabilizer includes, but is not limited to, at least one of the following: a hindered amine light stabilizer (e.g., light stabilizer 770, light stabilizer 622, light stabilizer 944, etc.), a benzophenone light stabilizer (e.g., UV531), or a benzotriazole light stabilizer.

[0070] The lubricant includes, but is not limited to, at least one of esters (e.g., polyethylene glycol esters, polyol esters), montanates, ethylenebisstearamide, or polyethylene wax.

[0071] The aforementioned release agent includes, but is not limited to, at least one of the following: inorganic release agents (e.g., talc powder, mica powder, clay, etc.), organic release agents (e.g., fatty acids, paraffin, glycerol, petrolatum, etc.), or polymeric release agents (e.g., silicone oil, polyethylene glycol, low molecular weight polyethylene, etc.).

[0072] The antistatic agent includes, but is not limited to, at least one of the following: a cationic antistatic agent (e.g., a quaternary ammonium salt), an anionic antistatic agent (e.g., alkyl sulfonates, phosphates), an amphoteric antistatic agent (e.g., an amphoteric imidazoline compound), a nonionic antistatic agent (e.g., hydroxyethylalkylamines, fatty acid amides, polyoxyethylenes, polyol esters), or a polymeric antistatic agent (e.g., polyethers).

[0073] As a preferred technical solution of the present invention, the polyester composition comprises, by weight, 50 to 95 parts by weight of aliphatic polyester (for example, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or any number in between, but preferably 52 to 92 parts, more preferably 56 to 82 parts), 1 to 20 parts by weight of a second polyester (for example, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, or any number in between, but preferably 1.5 to 15 parts, more preferably 2.5 to 8.5 parts), and polymer B It comprises 1 to 30 parts (for example, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 25, 26, 28, 30 parts, or any range between the above numbers, but preferably 9 to 27 parts, more preferably 21 to 26.5 parts) and 0 to 15 parts of an auxiliary agent (for example, 1, 2, 4, 6, 8, 10, 12, 14, 15 parts, or any range between the above numbers).

[0074] In the present invention, the method for producing the polyester composition includes the steps of mixing polymer A, polymer B, and an optional auxiliary agent, and extruding the mixture to obtain the polyester composition, wherein the extruder includes a reaction extruder, which may be a single-screw extruder, a twin-screw extruder, or a multi-screw extruder, the extrusion temperature is 140 to 220°C, and the screw rotation speed during extrusion is 200 to 500 rpm.

[0075] In a third aspect, the present invention provides a packaging film comprising an aliphatic polyester as described in the first aspect, or a polyester composition as described in the second aspect.

[0076] In the present invention, the packaging film may have other substances added to it, such as colorants, pigments, and inorganic fillers, depending on the actual needs. The pigments include, but are not limited to, titanium dioxide, and the inorganic fillers include, but are not limited to, talc powder, calcium carbonate, and kaolin.

[0077] Preferably, the degree of orientation of the packaging film is 0.7 to 1.6, more preferably 0.8 to 1.4, and more preferably 0.9 to 1.2.

[0078] In this invention, the degree of orientation of the packaging film refers to the ratio of the tear strength in the longitudinal direction to the tear strength in the transverse direction. The higher the degree of orientation, the stronger the tear resistance in the longitudinal direction and the weaker the tear resistance in the transverse direction, making it more prone to tearing in the transverse direction during use. The lower the degree of orientation, the weaker the tear resistance in the longitudinal direction and the stronger the tear resistance in the transverse direction, making it more prone to tearing in the longitudinal direction during use. The closer the degree of orientation is to 1, the more uniform the tear resistance in the longitudinal and transverse directions of the material becomes.

[0079] In this invention, the Elmendorf tear strength in the transverse and longitudinal directions of the packaging film is tested in accordance with ASTM D1922. The thickness of the test sample is 55 ± 3 μm. Next, the degree of orientation is obtained as the ratio of the Elmendorf tear strength in the longitudinal direction to the Elmendorf tear strength in the transverse direction.

[0080] In this invention, in accordance with ISO 527-2:2012, the tensile strength of the packaging film in the longitudinal direction is ≥18 MPa, the tensile strength in the transverse direction is ≥16 MPa, and more preferably, the tensile strength in the longitudinal direction is ≥20 MPa and the tensile strength in the transverse direction is ≥18 MPa.

[0081] In the present invention, when the biodegradability of the packaging film is ≥ 90%, the decomposition cycle is ≤ 21 weeks, and more preferably, the decomposition cycle is ≤ 15 weeks.

[0082] In this invention, the biodegradation rate and decomposition cycle of the packaging film are measured using the following method.

[0083] The initial mass of a packaging film measuring 10cm x 10cm and 55±3μm in length x width is tested and recorded as m0. The home composting test is conducted according to standard AS5810. Samples are taken once a week, sieved, and the remaining packaging film measuring 2cm x 2cm or larger is held in the sieve. The residue on the packaging film is washed, dried, and weighed, and the sample mass is recorded as m. n Record as follows: Biodegradability of packaging film [(m0-m n If [) / m0] ≥ 90%, record the corresponding resolution period n.

[0084] In this invention, the packaging film includes food packaging film, industrial packaging film, agricultural mulch film, shopping bags, garbage bags, and the like.

[0085] The aliphatic polyester, the polyester composition containing the aliphatic polyester, and the packaging film produced therefrom are all biodegradable.

[0086] In this invention, a substance or mixture of substances is considered to have the characteristic of "biodegradability" if it exhibits a biodegradability rate of at least 90%, as defined in DIN EN 13432.

[0087] According to DIN EN 13432, the composting process involves introducing CO2-free air into the maturing compost and subjecting it to specific temperature treatments. Here, biodegradability is defined as the biodegradation rate, expressed as the ratio of the net amount of CO2 released from the sample (minus the amount of CO2 released from compost without the sample) to the maximum amount of CO2 that the sample can release (calculated from the carbon content in the sample). Biodegradable polyesters and biodegradable polyester compositions typically show clear signs of decomposition, such as fungal growth, dissolution, and perforation, within just a few days after composting.

[0088] Other methods for determining biodegradability are also described in ASTM D5338 and ASTM D6400.

[0089] The numerical range described in this invention includes not only the point values ​​listed above, but also all point values ​​within the numerical range not listed above. Due to space limitations and for the sake of brevity, this invention does not exhaustively list all specific point values ​​included in the range. [Effects of the Invention]

[0090] Compared to conventional technology, the beneficial effects of the present invention are as follows:

[0091] The aliphatic polyester according to the present invention can be made into polybutylene succinate sebacate with uniform lateral and longitudinal tear properties by controlling the content of succinic acid and sebacic acid within a specific range. By using the polybutylene succinate sebacate as a base resin to produce a starch-based biodegradable material, the problems of anisotropy and poor uniformity of longitudinal and transverse tear properties in starch-based biodegradable materials are solved, and the material is ensured to have good tensile properties and biodegradability, meeting the requirements for composting at home. [Modes for carrying out the invention]

[0092] The technical solutions of the present invention will be further described below through specific embodiments. Those skilled in the art will understand that the embodiments described are merely to aid in understanding the present invention and should not be construed as particularly limiting the invention. In this invention, all materials used can be purchased commercially or prepared using conventional methods. Unless otherwise specified, the materials used in this invention are as follows:

[0093] 1,4-Butanediol: Purchased from Xinjiang MarkorChem Co., Ltd. Succinic acid: Purchased from Shandong Lanzian Biotechnology Co., Ltd. Sebacic acid: Purchased from Hengshui Jinghua Chemical Co., Ltd. Glycerol: Purchased from Aladdin. Tetrabutyl titanate: Purchased from Jianyi Chemical Import & Export Co., Ltd. Hexamethylene diisocyanate: Purchased from Aladdin. Starch: Purchased from Shandong Shouguang Juneng Jinyu Rice Development Co., Ltd. Polylactic acid: PLA, KB600 NF30, purchased from Zhuhai Jin Generating Materials Co., Ltd.

[0094] In this invention, the test methods for Mn, intrinsic viscosity, carboxyl content, and mole fractions of succinic acid residues and sebacic acid residues in aliphatic polyester are as follows.

[0095] 1. Mn is tested using gel permeation chromatography (GPC). A chromatography system is used with three tandem columns (particle size 5 μm, porosity 500 Å, 1000 Å, and 10000 Å, respectively) and a refractive index detector. Measurement is performed at 40°C with chloroform as the eluent (elution flow rate 1 mL / min) and polystyrene as the standard substance.

[0096] 2. The intrinsic viscosity test shall be performed in reference to standard GB / T 17931-1999. Specifically, 0.1250 ± 0.0002 g of the sample shall be added to 25 mL of a phenol / o-dichlorobenzene mixed solution in a weight ratio of 1:1, heated until the sample is completely dissolved, and then tested using an Ubbelohde viscometer at a test temperature of 25 ± 0.05 °C.

[0097] 3. The carboxyl content test is performed in reference to standard GB / T 32366-2015. Specifically, it is performed as follows: Dissolve 1 g of the sample in 50 mL of a mixed solvent of phenol and chloroform in a volume ratio of 2:3. Use a 0.01 mol / L potassium hydroxide ethanol solution as the standard titration solution and a 0.2% bromophenol blue solution as the indicator. Perform a blank test based on the above method for testing the carboxyl content of the sample. Test the sample twice in parallel, and the difference between the two test results must be 2 mol / t or less. The final result is the average of the two test results.

[0098] 4. Mole fraction is, 1 It can be tested by 1H NMR. Specifically, 20 mg of the aliphatic polyester sample is dissolved in 0.6 mL of deuterated chloroform, and then the sample is analyzed at room temperature using a Bruker AV 500 NMR spectrometer. 1 1H NMR is measured. Characteristic chemical schiff peaks of succinic acid residues and sebacic acid residues (the characteristic chemical schiff of succinic acid residues is approximately 2.63 ppm, representing the four hydrogen atoms on the two methylene-CH2-CH2- in succinic acid; the characteristic chemical schiff of sebacic acid residues is approximately 1.30 ppm, representing the eight hydrogen atoms on the four methylene-CH2-CH2-CH2- in the center of sebacic acid) are integrated, and the mole fractions of succinic acid residues and sebacic acid residues in the aliphatic polyester are obtained from the ratio of peak areas. Note that the content of succinic acid residues and sebacic acid residues in the aliphatic polyester shown in Table 1 is the content when the total molar amount of succinic acid residues and sebacic acid residues is set to 100 mol%. For example, if the integral area of ​​succinic acid residues is I1 and the integral area of ​​sebacic acid residues is I2, then the mole fraction of succinic acid residues in an aliphatic polyester is I1 / (I1+I2)×100%. Examples 1-13, Comparative Examples 1, 2

[0099] Examples 1 to 13 and Comparative Examples 1 and 2 each provide aliphatic polyesters, and the molecular structure composition, Mn, acid value, and intrinsic viscosity of the aliphatic polyesters are shown in Table 1.

[0100] [Table 1]

[0101] The methods for producing aliphatic polyesters according to Examples 1-13 and Comparative Examples 1 and 2 are as follows. Example 1

[0102] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 350 kg of succinic acid, 323 kg of sebacic acid, 575 kg of 1,4-butanediol, and 2.76 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 4 hours at a temperature of 200°C and a pressure of 1.1 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 1.1 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 110 min at a temperature of 243°C and a pressure of 0.6 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 80 minutes at a temperature of 245°C and a pressure of 1.1 mbar to obtain an aliphatic polyester. Example 2

[0103] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 373 kg of succinic acid, 300 kg of sebacic acid, 575 kg of 1,4-butanediol, and 2.76 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 4 hours at a temperature of 190°C and a pressure of 1.1 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 1.1 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 120 min at a temperature of 240°C and a pressure of 0.7 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 100 minutes at a temperature of 245°C and a pressure of 1.1 mbar to obtain an aliphatic polyester. Example 3

[0104] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 330 kg of succinic acid, 343 kg of sebacic acid, 575 kg of 1,4-butanediol, and 2.76 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 3.5 hours at a temperature of 180°C and a pressure of 0.9 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 1.1 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 100 min at a temperature of 242°C and a pressure of 0.6 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 85 minutes at a temperature of 243°C and a pressure of 1.3 mbar to obtain an aliphatic polyester. Example 4

[0105] A method for producing the aliphatic polyester is provided. The differences from Example 1 are as follows: Glycerol was not used in step (1), and the polycondensation reaction in step (3) was carried out for 60 minutes under conditions of a temperature of 243°C and a pressure of 1.1 mbar. In addition, after the polycondensation reaction in step (3), the obtained polycondensation product and hexamethylene diisocyanate (content: 0.3 wt% of the mass of the polycondensation product) were extruded in a reaction extruder at a temperature of 200°C for a residence time of 8 minutes. The remaining raw materials, steps, and polymerization process were all the same as in Example 1. Example 5

[0106] A method for producing the aliphatic polyester is provided. The differences from Example 1 are as follows. Step (1) includes the following steps. (1-1) 350 kg of succinic acid, 300 kg of 1,4-butanediol, and 2.76 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 4 hours at a temperature of 165°C and a pressure of 1.1 bar to obtain esterification product A. (1-2) 323 kg of sebacic acid and 275 kg of 1,4-butanediol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 3 hours at a temperature of 200°C and a pressure of 0.9 bar to obtain esterification product B. After mixing esterification product A and esterification product B, steps (2) and (3) were carried out. The remaining raw materials, steps, and polymerization process were all the same as in Example 1. Example 6

[0107] A method for producing the aliphatic polyester is provided. The differences from Example 1 are as follows: The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 70 minutes under conditions of a temperature of 250°C and a pressure of 1.4 mbar. The remaining raw materials, steps, and polymerization process were all the same as in Example 1. Example 7

[0108] A method for producing the aliphatic polyester is provided. The differences from Example 4 are as follows: After the polycondensation reaction in step (3), the obtained polycondensation product and hexamethylene diisocyanate (content: 0.46 wt% of the mass of the polycondensation product) were extruded in a reaction extruder at a temperature of 210°C for a residence time of 5 minutes. The remaining raw materials, steps, and polymerization process were all the same as in Example 4. Example 8

[0109] A method for producing the aliphatic polyester is provided. The differences from Example 1 are as follows: In step (1), the amount of glycerol added was 2.45 kg, and at the same time, the esterification reaction was carried out for 3 hours under conditions where the esterification temperature was adjusted to 190°C and the pressure to 1.0 bar, in order to obtain the esterified product. In step (3), the polycondensation reaction was carried out for 70 minutes under conditions of a temperature of 243°C and a pressure of 1.0 mbar. The remaining raw materials, steps, and polymerization process were all the same as in Example 1. Example 9

[0110] A method for producing the aliphatic polyester is provided. The differences from Example 1 are as follows: In step (3), the prepolymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 50 minutes at a temperature of 248°C and a pressure of 1.2 mbar. In step (4), the polycondensation product obtained in step (3) and hexamethylene diisocyanate (content: 0.25 wt% of the mass of the polycondensation product) were extruded in a reaction extruder at a temperature of 220°C for a residence time of 10 minutes. The remaining raw materials, steps, and polymerization process were all the same as in Example 1. Example 10

[0111] A method for producing the aliphatic polyester is provided. The differences from Example 1 are as follows: In step (1), glycerol was not used, and the esterification reaction was carried out for 3 hours under conditions where the esterification temperature was adjusted to 180°C and the pressure to 1.1 bar to obtain the esterified product. In step (3), the polycondensation reaction was carried out for 75 minutes under conditions where the temperature was 245°C and the pressure to 1.5 mbar. The remaining raw materials, steps, and polymerization process were all the same as in Example 1. Example 11

[0112] A method for producing the aliphatic polyester is provided. The differences from Example 1 are as follows: In step (3), the prepolymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 45 minutes at a temperature of 242°C and a pressure of 1.4 mbar. In step (4), the polycondensation product obtained in step (3) and hexamethylene diisocyanate (content: 0.70 wt% of the mass of the polycondensation product) were extruded in a reaction extruder at a temperature of 220°C for a residence time of 13 minutes. The remaining raw materials, steps, and polymerization process were all the same as in Example 1. Example 12

[0113] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 350 kg of succinic acid, 323 kg of sebacic acid, 575 kg of 1,4-butanediol, and 12.0 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 2 hours at a temperature of 180°C and a pressure of 1.1 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 0.8 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 120 min at a temperature of 235°C and a pressure of 0.5 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 70 minutes at a temperature of 244°C and a pressure of 0.9 mbar to obtain an aliphatic polyester. Example 13

[0114] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1-1) 350 kg of succinic acid, 300 kg of 1,4-butanediol, and 0.5 kg of pentaerythritol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 3 hours at a temperature of 160°C and a pressure of 1.1 bar to obtain esterification product A. (1-2) 323 kg of sebacic acid and 275 kg of 1,4-butanediol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 4 hours at a temperature of 190°C and a pressure of 1.0 bar to obtain esterification product B. (2) The mixture of esterification product A obtained in step (1-1) and esterification product B obtained in step (1-2) was transferred to a vertical reactor with a stirring function, 1.0 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 105 mins at a temperature of 240°C and a pressure of 0.7 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to a polycondensation reaction for 70 minutes at a temperature of 242°C and a pressure of 1.1 mbar to obtain the polycondensation product. (4) The polycondensation product obtained in step (3) and hexamethylene diisocyanate (content: 0.57 wt% of the mass of the polycondensation product) were extruded in a reaction extruder at a temperature of 180°C for a residence time of 11 minutes. The remaining raw materials, steps, and polymerization process were all the same as in Example 1. Comparative Example 1

[0115] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 350 kg of succinic acid, 245 kg of sebacic acid, 534 kg of 1,4-butanediol, and 2.46 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 3.5 hours at a temperature of 200°C and a pressure of 1.1 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 0.92 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 120 min at a temperature of 245°C and a pressure of 0.52 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 90 minutes at a temperature of 246°C and a pressure of 1.3 mbar to obtain an aliphatic polyester. Comparative Example 2

[0116] Specifically, the present invention provides a method for producing the aliphatic polyester, comprising the following steps. (1) 250 kg of succinic acid, 345 kg of sebacic acid, 480 kg of 1,4-butanediol, and 2.46 kg of glycerol were physically mixed. After mixing was complete, the mixture was transferred to an esterification reactor and esterified for 4 hours at a temperature of 190°C and a pressure of 1.1 bar to obtain the esterification product. (2) The esterification product obtained in step (1) was transferred to a vertical reactor with a stirring function, 0.92 kg of tetrabutyl titanate was added, and the prepolymerization reaction was carried out for 130 min at a temperature of 243°C and a pressure of 0.52 bar to obtain the prepolymerization product. (3) The preliminary polymerization product obtained in step (2) was transferred to a horizontal reactor with a stirring function and subjected to polycondensation reaction for 80 minutes at a temperature of 246°C and a pressure of 1.2 mbar to obtain an aliphatic polyester. Application examples 1-13, comparative application examples 1, 2

[0117] Application Examples 1-13 and Comparative Application Examples 1 and 2 each provide polyester compositions. The polyester composition comprises, by weight, 63 parts aliphatic polyester, 2 parts polylactic acid, 27 parts starch, 4 parts glycerol, 3 parts water, and 1 part other additive (0.5 parts of a composite antioxidant consisting of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, and 0.5 parts of ethylenebisstearate amide, which is a lubricant). The aliphatic polyester is provided in Examples 1-13 and Comparative Examples 1-2, respectively. The method for producing the polyester composition includes mixing each component according to the blending amounts, adding them to a twin-screw extruder (aspect ratio 48:1, diameter 40 mm), melt-mixing, and extrusion granulation. The extrusion temperatures were as follows: Zone 1 120°C, Zone 2 160°C, Zones 3-9 180°C, Zone 10 170°C, Zone 11 170°C, die head 190°C, screw rotation speed 380 rpm, and vacuum -0.60 kg / cm². 2 Therefore, a polyester composition was obtained. Performance testing

[0118] The polyester compositions provided in Application Examples 1-13 and Comparative Application Examples 1-2 were inflated to obtain packaging films. The uniformity of tear resistance, decomposition cycle, and tensile strength of the packaging films were tested. The specific test results are shown in Table 2.

[0119] The process parameters for the inflation film were as follows: the screw aspect ratio was 32:1, a spiral flow type die head was used, the air ring was a double outlet air ring, the inflation temperature was set to 140°C, the blow-up ratio was 3.5, and the inflation film thickness was 55±3μm. Subsequently, the uniformity of tear resistance, decomposition cycle, and tensile strength were tested.

[0120] (1) Uniformity of tear resistance: Under the conditions of 25±5°C and 55±5% humidity, the transverse direction (ε TD ) and longitudinal direction (ε MD ) Elmendorf tear strength of samples was tested according to ASTM D1922-2015 standard, and the degree of orientation was calculated. Degree of orientation = ε MD / ε TD . (2) Decomposition period:

[0121] The sample was weighed, the aliphatic polyester was molded into a product with a size of 10 cm × 10 cm to obtain the initial mass of the sample, which was recorded as m0. The home composting test was carried out in accordance with standard AS5810. The sample was collected once a week, after sieving, the packaging film with length × width of 2 cm × 2 cm or larger remaining on the sieve was retained. The residue on the packaging film was washed, dried, weighed, and the sample mass was recorded as m n . When the biodegradation rate of the sample [(m0 - m n ) / m0] ≧ 90%, the corresponding decomposition period n was recorded.

[0122] (3) Tensile strength: Tested in accordance with ISO 527-2:2012.

[0123]

Table 2

[0124] As can be seen from Table 2, the aliphatic polyester according to the present invention, by controlling the mole fraction of succinic acid and sebacic acid within a specific range, has excellent uniformity in longitudinal and transverse tear properties, and the degree of orientation approaches 1. At the same time, it also has good tensile properties, and under home composting conditions, it has a relatively high biodegradation rate and a short decomposition period, which meets the requirements of home composting.

[0125] The specific embodiments described above further illustrate the object, technical solution, and beneficial effects of the present invention. These are merely specific embodiments of the present invention and do not limit it. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are also covered by the present invention.

Claims

1. An aliphatic polyester comprising a dibasic acid residue and a diol residue, The aforementioned dibasic acid residue is, as a residue, a1): Based on the total mole fraction of a1) and a2) at 100 mol%, 61.2 to 69 mol% succinic acid residues, a2): Based on the total mole fraction of a1) and a2) of 100 mol%, it contains 31 to 38.8 mol% of sebaciate residues, The aliphatic polyester is characterized in that the diol residue is selected from at least a dibasic acid residue and an equimolar amount of a 1,4-butanediol residue.

2. The aforementioned dibasic acid residue is, as a residue, a1): Based on the total mole fraction of a1) and a2) at 100 mol%, 63.5 to 67.5 mol% succinic acid residues, a2): The aliphatic polyester according to claim 1, characterized in that it contains 32.5 to 36.5 mol% of sebaciate residues based on a total mole fraction of 100 mol% of a1) and a2).

3. The aliphatic polyester according to claim 1, characterized in that the number average molecular weight of the aliphatic polyester is 30,000 to 150,000, preferably 45,000 to 120,000, and more preferably 58,000 to 79,000.

4. The aliphatic polyester according to claim 1, characterized in that, in accordance with GB / T 32366-2015, the carboxyl content of the aliphatic polyester is <35 mol / t, preferably <28 mol / t, and more preferably 5 to 20 mol / t.

5. The aliphatic polyester according to claim 1, characterized in that, in accordance with GB / T 17931-1999, the intrinsic viscosity of the aliphatic polyester is 1.38 to 2.32 dL / g, preferably 1.5 to 2.2 dL / g.

6. A polyester composition comprising polymer A and polymer B, wherein polymer A comprises the aliphatic polyester described in claim 1.

7. The polymer A further comprises a second polyester, Preferably, the second polyester comprises at least one of polylactic acid, aliphatic-aromatic polyester, or other aliphatic polyester. Preferably, the aliphatic-aromatic polyester comprises at least one of polybutylene succinate terephthalate, polybutylene adipate terephthalate, polybutylene sebacate terephthalate, or polybutylene adipate difrangiccarboxylate. Preferably, the other aliphatic polyester comprises at least one of polybutylene succinate, polybutylene succinate adipate, or polybutylene sebacate. Preferably, the polymer B comprises at least one of the following: starch, cellulose, chitin, chitosan, alginate ester, protein, gelatin, natural rubber, lignin, or a derivative of the aforementioned substances. Preferably, the polyester composition according to claim 6 further comprises an auxiliary agent.

8. The polyester composition according to claim 6, characterized in that the polyester composition comprises, by weight, 50 to 95 parts by aliphatic polyester, 1 to 20 parts by secondary polyester, 1 to 30 parts by polymer B, and 0 to 15 parts by auxiliary agent.

9. A packaging film, characterized in that the packaging film comprises an aliphatic polyester according to any one of claims 1 to 5, or a polyester composition according to any one of claims 6 to 8.

10. The packaging film according to claim 9, characterized in that the degree of orientation of the packaging film is 0.7 to 1.6, more preferably 0.8 to 1.4, and more preferably 0.9 to 1.2.